Planet-friendly school meals: opportunities to improve children’s health and leverage change in food systems - Pastorino, Silvia; Backlund, Ulrika; Bellanca, Raffaella; Hunter, Danny; Kaljonen, Minna; Singh, Samrat; Vargas, Melissa; Bundy, Donal (Elsevier, 2024)
Food systems are facing a global crisis. Most countries are falling behind rather than progressing toward achieving the seven global nutrition targets set for 2030, while unsustainable food production and consumption patterns have contributed to depletion and pollution of natural resources and climate change, further compromising food security and nutrition. Children are disproportionately affected with 1 billion children at high risk of food insecurity. Low-income countries will be the most affected by these changes despite having contributed the least.